PERIODISITAS PARASIT FILARIASIS DI DESA KARYA MAKMUR KABUPATEN OKU TIMUR TAHUN 2007 - Santoso Santoso (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Study on the periodicity of filarial larvae in Karya Makmur Village, Batumarta VIII Health Care East OKU has been conducted in 2007. The objectives of the study were to identify the prevalence of microfilaria rate (Mf rate), filarial larvae species and periodicity of filarial larvae. The number of people examined were 381 people and out of this number 4 people were mf positive. The Mf rate was 1.05%. Periodicity study was done in 5 positive persons. Blood was taken from each patient every 2 hours in 24 hours. The highest density was 8.95 per mm³ found at 21.00. According to the analysis it was found that the parasite was nocturnally periodic in 3 patients and not found in 2 patients.